New isotope constraints on the Mg oceanic budget point to cryptic modern dolomite formation - Netta Shalev (Nature Portfolio, 2019)
Earth’s carbon cycle and oceanic magnesium cycle are controlled by processes such as weathering, volcanism and precipitation of carbonates, such as dolomite. Here, the authors contradict the view that modern dolomite formation is rare and suggest instead that dolomite accounts for ~40–60% of the global oceanic Mg output in the last 20 Ma.